The Improvisation of Strategies for Academic Self-Regulation During the Performance Phase of Arabic Learning - Hunainah, Hunainah (Mayada: al-Multaqa al-Ilmy al-Alamy lil-Dirasat al-Arabiyah; Vol 1 No 1 (2023): مجموعة البحوث - الملتقى العلمي العالمي للدراسات العربية, 2024)
استراتيجيات التنظيم الذاتي الأكاديمي المطبقة في تعلم اللغة العربية بين الطالبات في معهد نور الجديد تتضمن ممارسة اللغة الشفوية. هذا يشمل إثراء المفردات من خلال المراقبة، وتعليم الأقران في الصف أو في مجموعات صغيرة، وتيسير الأنشطة اللغوية باستخدام مقاربات شخصية أو جماعية متنوعة. أجريت دراسة الحالة النوعية هذه في مدرسة نور الجديد بيتون الإسلامية من خلال جمع البيانات من خلال الملاحظة، والمقابلات، وتحليل الوثائق. أسفر البحث عن: (1) مخطط للسيطرة على الذات والمراقبة الذاتية ضمن القيادة الذاتية الأكاديمية لطلاب نور الجديد بيتون في تعلم اللغة العربية، موضحا العمليات الفرعية الحالية؛ (2) تحديد أنواع السيطرة على الذات والمراقبة الذاتية السائدة ضمن القيادة الذاتية الأكاديمية لطالبات نور الجديد بيتون الدارسات للغة العربية. الاستنتاج الذي توصلت إليه هذه الدراسة هو أن مجموعة متنوعة من الأنشطة اللغوية الممتعة يمكن أن تؤدي إلى استراتيجيات متنوعة ومحسنة The academic self-regulation strategies applied in Arabic language learning among female students at Nurul Jadid Institute involve practicing spoken language among themselves. This encompasses vocabulary enrichment through monitoring, teaching peers in class or smaller groups, and facilitating linguistic activities using various personal or group approaches. This qualitative case study conducted at Nurul Jadid Paiton Islamic boarding school involved data collection through observation, interviews, and document analysis. The research resulted in: (1) an outline of self-control and self-observation within the academic self-regulation of Nurul Jadid Paiton students learning Arabic, detailing existing subprocesses; (2) identification of the predominant types of self-control and self-observation within the academic self-regulation of Nurul Jadid Paiton students studying Arabic. The conclusion drawn from this study is that a variety of enjoyable linguistic activities can lead to improvised strategies.